Phenolics and antioxidant properties of bayberry (Myrica rubra Sieb. et Zucc.) pomace - Zhou, S.; Fang, Zhongxiang; Lü, Y.; Chen, J.; Liu, D.; Ye, X. (Elsevier BV, 2009)
Five cultivars of Myrica rubra, Biqi, Wandao, Dongkui, Dingao, and Zaodamei, were collected to analyze the phenolic compounds and evaluate the antioxidant properties of bayberry pomaces. The main anthocyanin was cyanidin-3-o-glucoside (3073.3-6219.2 mg/kg dry weight (DW)) and the main flavonol was quercetin-3-o-glucoside (296.2-907.9 mg/kg dry weight). Quercetin and myricetin were also found in the bayberry pomaces, and quercetin deoxyhexoside and myricetin deoxyhexoside were tentatively identified. The dominant phenolic acids were gallic acid (102.9-241.7 mg/kg dry weight) and protocatechuic acid (29.5-57.2 mg/kg dry weight). Other phenolic acids such as p-hydroxybenzoic, vanillic, caffeic, p-coumaric, and ferulic acids were also present in the bayberry pomaces, whereas, chlorogenic acid was only detected in Dongkui (1.58 mg/kg dry weight). The antioxidant activity of Wandao was the strongest of the five cultivars, whereas the activity of Dongkui was the weakest, and a significant positive relationship was observed between antioxidant activity and total phenolic content or total anthocyanins. © 2008 Elsevier Ltd. All rights reserved.